Investigating the Direct Meltwater Effect in Terrestrial Oxygen‐Isotope Paleoclimate Records Using an Isotope‐Enabled Earth System Model. Issue 24 (28th December 2017) - Zhu, Jiang; Liu, Zhengyu; Brady, Esther C.; Otto‐Bliesner, Bette L.; Marcott, Shaun A.; Zhang, Jiaxu; Wang, Xianfeng; Nusbaumer, Jesse; Wong, Tony E.; Jahn, Alexandra; Noone, David
Abstract: Variations in terrestrial oxygen‐isotope reconstructions from ice cores and speleothems have been primarily attributed to climatic changes of surface air temperature, precipitation amount, or atmospheric circulation. Here we demonstrate with the fully coupled isotope‐enabled Community Earth System Model an additional process contributing to the oxygen‐isotope variations during glacial meltwater events. This process, termed "the direct meltwater effect, " involves propagating large amounts of isotopically depleted meltwater throughout the hydrological cycle and is independent of climatic changes. We find that the direct meltwater effect can make up 15–35% of the δ 18 O signals in precipitation over Greenland and eastern Brazil for large freshwater forcings (0.25–0.50 sverdrup (10 6 m 3 /s)). Model simulations further demonstrate that the direct meltwater effect increases with the magnitude and duration of the freshwater forcing and is sensitive to both the location and shape of the meltwater. These new modeling results have important implications for past climate interpretations of δ 18 O. Key Points: A portion of the δ 18 O signal in land‐based paleoclimate proxies can be attributed to the direct meltwater effect instead of climatic changes The direct meltwater effect can make up 15‐35% of the δ 18 O signals in precipitation in Greenland and eastern Brazil for large meltwater events The direct meltwater effect increases with the magnitude and duration of the freshwater forcing and is sensitive to location and shape dependent